System dynamics of active and passive postural changes: Insights from principal dynamic modes analysis of baroreflex loop. (1st September 2018) - Shahzad, Tariq; Saleem, Saqib; Usman, Saeeda; Mirza, Jawad; Islam, Qamar-ul; Ouahada, Khmaies; Marwala, Tshilidzi
Abstract: The baroreflex being a key modulator of cardiovascular control ensures adequate blood pressure regulation under orthostatic stress which otherwise may cause severe hypotension. Contrary to conventional baroreflex sensitivity indices derived across a-priori traditional frequency bands, the present study is aimed at proposing new indices for the assessment of baroreflex drive which follows active (supine to stand-up) and passive (supine to head-up tilt) postural changes. To achieve this, a novel system identification approach of principal dynamic modes (PDM) was utilized to extract data-adaptive frequency components of closed-loop interactions between beat-to-beat interval and systolic blood pressure recorded from 10 healthy humans. We observed that the gain of low-pass global PDM of cardiac arm (:feedback reflex loop, mediated by pressure sensors to adjust heart rate in response to arterial blood pressure), and 0.2 Hz global PDM of mechanical arm (:feed-forward pathways, originating changes in arterial blood pressure in response to heart rate variations) may function as potential markers to distinguish active and passive orthostatic tests in healthy subjects. Highlights: Arterial baroreflex ensures blood pressure regulation. Novel indices are proposed for baroreflex role in orthostatic tests. Cardiac and mechanical arms of baroreflex interact in a closed-loop fashion. Both arms contribute along different frequency dynamics for postural challenges.